Tata Cara Wakaf Hak Milik Setelah Berlakunya Undang-Undang Nomor 41 Tahun 2004 Tentang Wakaf - Abdullah, Junaidi (ZISWAF, 2018)
Waqf is horizontal social worship and can be made for the welfare of the people. Waqf can be in the form of immovable objects such as land that has become the propertyBefore the issuance of Law number 41 of 2004 concerning Waqf, the implementation of waqf in the community when the land of ownership was granted both for mosques, prayer rooms and schools without being registered and not registered, so that when the Wakak died there would be problems relating to land that had represented, usually the heirs demand the return of waqf land that has been represented by their parents. So to avoid this problem, the regulations from the government appear to regulate or answer the problems mentioned above.The procedure for land waqf after the enactment of Law No. 41 of 2004 concerning Waqf is through the waqf pledge process by the Wakif, then a waqf pledge is made which directly pledges before PPAIW or can be represented by making a power of attorney and strengthened by two witnesses or deed of replacement for the waqf certificate for the Wakif who has passed away. After being made AIW or APAIW registered with the BPN with the conditions. After completion, it was announced at the general register of the Ministry of Religion office and BWI.